Cost‐Effectiveness of Combination Disease‐Modifying Antirheumatic Drugs Versus Tumor Necrosis Factor Inhibitors in Active Rheumatoid Arthritis: A Pragmatic, Randomized, Multicenter Trial. Issue 3 (27th February 2020) - Patel, Anita; Heslin, Margaret; Scott, David L.; Stringer, Dominic; Birrell, Fraser; Ibrahim, Fowzia
Abstract : Objective: To determine whether intensive combinations of conventional synthetic disease‐modifying antirheumatic drugs (csDMARDS) achieve similar clinical benefits more cheaply than high‐cost biologics such as tumor necrosis factor inhibitors (TNFi) in patients with active rheumatoid arthritis (RA) whose illness has failed to respond to methotrexate and another DMARD. Methods: We used within‐trial cost‐effectiveness and cost‐utility analyses from health and social care and 2 societal perspectives. Participants were recruited into an open‐label, 12‐month, pragmatic, randomized, multicenter, 2‐arm, noninferiority trial in 24 rheumatology clinics in England and Wales. Costs were linked with the Health Assessment Questionnaire (HAQ; primary outcome) and quality‐adjusted life years derived from 2 measures (Short‐Form 36 health survey and EuroQol 5‐domain 3‐level instrument). Results: In total, 205 participants were recruited, 104 in the csDMARD arm and 101 in the TNFi arm. Participants in the csDMARD arm with poor response at 6 months were offered TNFi; 46 participants (44%) switched. Relevant cost and outcome data were available for 93% of participants at 6‐month follow‐up and for 91–92% of participants at 12‐month follow‐up. The csDMARD arm had significantly lower total costs from all perspectives (6‐month health and social care adjusted mean difference –£3, 615 [95% confidence interval (95% CI) –4, 104, –3, 182]; 12‐month health and social care adjusted mean difference –£1, 930 [95% CI –2, 599, –1, 301]). The HAQ score showed benefit to the csDMARD arm at 12 months (–0.16 [95% CI –0.32, –0.01]); other outcomes/follow‐ups showed no differences. Conclusion: Starting treatment with csDMARDs, rather than TNFi, achieves similar outcomes at significantly lower costs. Patients with active RA and who meet the National Institute for Health and Care Excellence criteria for expensive biologics can be treated with combinations of intensive csDMARDs in a cost‐effective manner.